2010
DOI: 10.1016/j.jmb.2009.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Adenine Ligand on the Stabilization of the Secondary and Tertiary Interactions in the Adenine Riboswitch

Abstract: Riboswitches are RNA-based genetic control elements that function via a conformational transition mechanism when a specific target molecule binds to its binding pocket. To facilitate an atomic detail interpretation of experimental investigations on the role of the adenine ligand on the conformational properties and kinetics of folding of the add adenine riboswitch, molecular dynamics (MD) simulations were performed in both the presence and absence of the ligand. In the absence of ligand, structural deviations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 56 publications
12
61
0
Order By: Relevance
“…The sample structures in the absence of the ligand are some of the possible conformations accessible to the system. However, after the removal of the ligand, the rootmean-square fluctuation of the residues in the junction area increases by 20% (data not shown), in agreement with previous MD studies (Sharma et al 2009;Villa et al 2009;Priyakumar and MacKerell 2010). The bases A21 and A19 (helix P1) and U74 (ligand recognition residue located in junction area J3-1) and U75 (helix P1) become more exposed to solvent than in the complex with adenine.…”
Section: Add A-riboswitch Aptamer Bound To the Cognate Ligandsupporting
confidence: 89%
See 1 more Smart Citation
“…The sample structures in the absence of the ligand are some of the possible conformations accessible to the system. However, after the removal of the ligand, the rootmean-square fluctuation of the residues in the junction area increases by 20% (data not shown), in agreement with previous MD studies (Sharma et al 2009;Villa et al 2009;Priyakumar and MacKerell 2010). The bases A21 and A19 (helix P1) and U74 (ligand recognition residue located in junction area J3-1) and U75 (helix P1) become more exposed to solvent than in the complex with adenine.…”
Section: Add A-riboswitch Aptamer Bound To the Cognate Ligandsupporting
confidence: 89%
“…The simulations in the absence of the cognate ligand allow us to identify which interactions are stabilized by the presence of the ligand. MD simulations together with a classical force field have previously been successfully used to investigate the structure of the purine-aptamer in the presence and absence of the cognate ligands (Sharma et al 2009;Villa et al 2009;Priyakumar and MacKerell 2010). Here, we apply umbrella sampling techniques to induce the breaking of the tertiary interaction between the L2 and L3 loops.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, MD has elucidated chemical features that stabilize ligand binding, the interactions that stabilize conformational endpoints, and features that facilitate conformational switching. Studies have been conducted on the SAM-I riboswitch (Huang et al 2009;Stoddard et al 2010;Doshi et al 2012;Hayes et al 2012;Huang et al 2013;Xue et al 2015), the SAM-II riboswitch (Kelley and Hamelberg 2010;Doshi et al 2012), the guanine riboswitch (Villa et al 2009;Sund et al 2014), the adenine riboswitch (Sharma et al 2009;Priyakumar and MacKerell 2010;Nozinovic et al 2014;Sund et al 2014), the GlmS riboswitch (Banáš et al 2010;Xin and Hamelberg 2010), and the preQ 1 -I and preQ 1 -III riboswitches (Petrone et al 2011;Banáš et al 2012;Eichhorn et al 2012;Gong et al 2014;Liberman et al 2015). Overall, these studies show the feasibility of using MD to understand riboswitch function and provide an opportunity to look for common themes in ligand binding and conformational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Using a self-organized polymer model with the Langevin dynamics, Lin and Thirumalai 14 described force-triggered unfolding of this system and obtained the same unfolding sequence as the experimental observation. Priyakumar and MacKerell 16 performed a 40 ns all-atom molecular dynamics (MD) simulation to investigate the unfolding behavior in both presence and absence of ligand, but the complete unfolding process was not produced and only structural deviations were observed in the J23 junction and P1 stem. In addition, some investigations have concentrated on the roles of adenine ligand on the structural stability of add A-riboswitch.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that the ligand binding plays a critical role in stabilizing the binding pocket, especially for the folded P1 stem. 11,16,17 While the all-atom MD simulation can provide useful information on the fluctuations and conformational changes of biomacromolecules, it is generally difficult to obtain a complete folding/unfolding picture through MD due to the prohibitive computational costs.…”
Section: Introductionmentioning
confidence: 99%